Glycogen supercompensation in skeletal muscle after cycling or running followed by a high carbohydrate intake the following days: a systematic review and meta-analysis - Solem, Kristian; Clauss, Matthieu; Jensen, Jørgen (Frontiers in Physiology, 2025)
IntroductionBergström and Hultman demonstrated that exhaustive exercise depleting muscle glycogen followed by three days on a carbohydrate-rich diet resulted in a doubling of the glycogen content. Although many studies have confirmed this finding, the magnitude of glycogen supercompensation and the mechanisms behind elevated glycogen content after exercise remain unclear. This systematic review meta-analyzed investigations on muscle glycogen supercompensation after exercise and 3–5 days on a high-carbohydrate diet. Meta-regression analyses were conducted to explore the influence of specific variables on muscle glycogen supercompensation.MethodsA systematic search was performed for published studies in PubMed and Web of Science in March 2025. Inclusion criteria were: 1) reported basal glycogen values after a mixed diet; 2) included an exercise session prior to the dietary intervention; 3) utilized high carbohydrate intake after exercise to supercompensate glycogen stores; 4) measured muscle glycogen content after 3–5 days on a high-carbohydrate diet; and 5) reported quantitative data on glycogen. Data were extracted to compare muscle glycogen supercompensation following cycling and running exercises, followed by a 3–5-day high-carbohydrate diet. Meta-analyses were performed using the mean difference (MD) with 95% confidence intervals (CI).ResultsA total of 30 studies published between 1966 and 2020 were included, comprising 319 participants (271 males and 48 females). Glycogen increased by 269.7 ± 29.2 mmol⋅kg−1 dry weight (dw) (95%CI [212.4, 327.0]; p < 0.001) after cycling exercise and by 156.5 ± 48.6 mmol⋅kg−1 dw (95%CI [61.3, 251.7]; p = 0.001) after running exercise. Muscle glycogen supercompensation after cycling was positively associated with percent carbohydrate in the diet (p < 0.001) and negatively associated with basal glycogen concentration (p = 0.011) and glycogen concentration after exercise (p < 0.001).ConclusionMuscle glycogen supercompensation occurs following both cycling and running after 3–5 days on a high-carbohydrate diet, with a greater magnitude observed after cycling compared to running. The magnitude of glycogen supercompensation after cycling is influenced by basal glycogen levels, glycogen content after exercise, and the relative carbohydrate content of the diet.